Osteoblast and osteoclast responses to A/B type carbonate-substituted hydroxyapatite ceramics for bone regeneration. (6th June 2017) - Germaini, Marie-Michèle; Detsch, Rainer; Grünewald, Alina; Magnaudeix, Amandine; Lalloue, Fabrice; Boccaccini, Aldo R; Champion, Eric
Abstract: The influence of carbonate substitution (4.4 wt%, mixed A/B type) in hydroxyapatite ceramics for bone remodeling scaffolds was investigated by separately analyzing the response of pre-osteoblasts and osteoclast-like cells. Carbonated hydroxyapatite (CHA) (Ca9.5 (PO4 )5.5 (CO3 )0.5 (OH)(CO3 )0.25 -CHA), mimicking the chemical composition of natural bone mineral, and pure hydroxyapatite (HA) (Ca10 (PO4 )6 (OH)2 -HA) porous ceramics were processed to obtain a similar microstructure and surface physico-chemical properties (grain size, porosity ratio and pore size, surface roughness and zeta potential). The biological behavior was studied using MC3T3-E1 pre-osteoblastic and RAW 264.7 monocyte/macrophage cell lines. Chemical dissolution in the culture media and resorption lacunae produced by osteoclasts occur with both HA and CHA ceramics, but CHA exhibits much higher dissolution and greater bioresorption ability. CHA ceramics promoted a significantly higher level of pre-osteoblast proliferation. Osteoblastic differentiation, assessed by qRT-PCR of RUNX2 and COLIA2, and pre-osteoclastic proliferation and differentiation were not significantly different on CHA or HA ceramics but cell viability and metabolism were significantly greater on CHA ceramics. Thus, the activity of both osteoclast-like and osteoblastic cells was influenced by the carbonate substitution in the apatite structure. Furthermore, CHA showed a particularly interesting balance between biodegradation, by osteoclasts and chemical dissolution, and osteogenesis through osteoblasts' activity, to stimulate bone regeneration. It is hypothesized that this amount of 4.4 wt% carbonate substitution leads to an adapted concentration of calcium in the fluid surrounding the ceramic to stimulate the activity of cells. These results highlight the superior biological behavior of microporous 4.4 wt% A/B CHA ceramics that could beneficially replace the commonly used HA of biphasic calcium phosphates for future applications in bone tissue engineering.